Factor structure and descriptive characteristics of the Croatian version of the revised Negative Acts Questionnaire (NAQ-R) as applied in the workplace, on a sample of police officers in the Split-Dalmatia Police District : Faktorska struktura i deskriptivna obilježja hrvatske verzije revidiranog upitnika negativnih ponašanja (NAQ-R) na radnom mjestu na uzorku policijskih službenika u PU Splitsko-dalmatinskoj - Radošević, Željka (Array, 2018)
Mobbing has been recognized as a psychosocial risk to the mental health of employees, but also as an organizational problem that has been the object of attention among scholars in sociological, psychological, medical, and criminologist sciences. This study is the preparatory phase of the implementation of The Negative Acts Questionnaire-Revised (NAQ-R, Einarsen, Hoel and Notelaers, 2009)which tests for exposure to harassment in the workplace. The main aim of the study was to determine whether the instruments are applicable to the sample of Croatian employees, by means of testing the factor structure and internal reliability of the said questionnaire. The sample encompassed 209 police officers of both genders in the Split-Dalmatia Police District, and the data were acquired by means of a survey. We used descriptive statistics to show the characteristics of the sample and to analyse the findings, and we tested the factor structure by utilizing principal factor analysis, relying on the Kaiser-Guttman criterion. We tested the internal reliability of the sample with the Cronbach’s Alpha coefficient. The results suggest that there is a two-factor structure in the questionnaire, with the first factor referring to harassment aimed at the employee’s personality, and the second factor referring to harassment that is aimed at the employee’s work. Cronbach’s Alpha coefficient shows a high level of reliability (α = 0.959).